Effect of Antibiotic Therapy on the Sensitivity of Etiological Diagnostic Methods in Patients with Infective Endocarditis after Surgery - E. O. Kotova; A. Yu. Moiseeva; Zh. D. Kobalava; E. A. Domonova; A. S. Pisaruk; O. Yu. Silveistrova; P. V. Kakhktsyan; V. V. Vladimirov (Рациональная фармакотерапия в кардиологии, 2023)
Aim. Assessment of impact  of the duration  of preoperative  antimicrobial  therapy  (AMT) on the sensitivity  of microbiological examination and polymerase  chain reaction (PCR) of blood/tissues of resected valves in operated patients with infective endocarditis  (IE).Materials and methods. 52 operated patients with active IE were included prospectively (Duke criteria, 2015). All patients underwent microbiological examination of blood  before  admission  to the cardiac  surgery  hospital,  as well as parallel  simultaneous microbiological examination and  PCR  of blood/tissues of excised  valves,  followed  by Sanger  sequencing. The duration  of preoperative  treatment  was  calculated  from the first day of AMT according to IE diagnosis to the day of surgery.Results. The causative agent of IE was established in 84.6% (n=44) patients by means of complex etiological diagnosis. A significant  decrease in the sensitivity of microbiological examination of venous blood was revealed when performed  in the period before and after hospitalization to a surgical hospital (up 44.2% to 17.3%, p<0.05). When comparing microbiological examination of blood/tissues of resected valves and PCR of blood/tissues of resected valves, molecular biological  methods demonstrated the greatest sensitivity, with a great advantage when examining the tissues of resected valves (17.3% and 19.2% vs. 38.5% and 75.0%, respectively;  p<0.001). The microbiological examination of venous blood performed  at an early date before admission  to the cardiac  surgery  hospital was comparable in sensitivity to the PCR blood test performed  at a later date after prolonged AMT,  and significantly less sensitive in relation to the PCR of resected valve tissues [44.2% and 38.5% (p>0.05) vs. 75.0% (p<0.05)]. In course of AMT 1-28 days,  there were comparable results of microbiological examination with PCR blood examination and significantly better results of PCR of resected valve tissues [31.0% and 34.5% and 41.4% (p>0.05) vs 72.4% (p<0.001), respectively], and with AMT ≥ 29 days, microbiological examination of any biological  material was negative  in all patients,  and PCR of blood/tissues of resected valves retained high sensitivity (0% and 0% vs. 34.8% and 78.3%, respectively; p<0.01).Conclusion. Long-term preoperative AMT significantly reduced the sensitivity of microbiological examination of resected valve blood/tissue in operated patients with IE, whereas PCR of resected valve blood/tissue was highly sensitive even with preoperative AMT for more than 29 days.